The Importance of Financial Literacy Knowledge For Elementary School Students In 21st Century - Perdanasari, Ayu; Sudiyanto, Sudiyanto; Octoria, Dini (Universitas Nusantara PGRI Kediri, 2019)
life in the 21st century requires a variety of skills that an individual must master in order to become a successful person in life. Skills in managing finances are needed. Therefore, the need for financial literacy knowledge is taught early, especially in schools so that it will accumulate into adulthood. This article aimed to explain the importance of financial literacy knowledge for elementary school students in the 21st century. Data collection used observation, literature study, and documentation. Data sources from informants and documents. Data analysis used qualitative data analysis of interactive models. The findings showed that students at elementary schools prefer to buy objects that are desired rather than needed. This shows the importance of financial literacy knowledge for elementary school students. This is supported by the results of a literature study that financial literacy knowledge will be useful in managing students' finances for now and in the future. Therefore, it is expected that the role of the teacher in providing teaching material about financial literacy in accordance with the stages of student development.